The Societal Impact of Herpes Zoster and Postherpetic Neuralgia on Patients, Life Partners, and Children of Patients in Germany - Thomas Weinke; Andrea Glogger; Isabelle Bertrand; Kati Lukas (The Scientific World Journal)
The aim of this study was to assess the impact of herpes zoster (HZ) and postherpetic neuralgia (PHN) on the daily activities of patients and family members who care for them. Some former patients and family members participated in face-to-face interviews or in a T-group meeting (qualitative phase) and some participated in telephone interviews (quantitative phase). They all expressed feelings of helplessness and frustration mixed with depression, sadness, or rage. Many of the former patients said their lives stopped, in contrast to family members who said that their lives were busy and stressful. Family members caring for patients with PHN were more psychologically stressed than those caring for patients with HZ. Although former patients appreciated the psychological and emotional support given by their family members, they underestimated the impact that their disease had on them. Former patients and their family never forgot this illness and its considerable impact on their lives, particularly when PHN occurred. We need to raise the awareness of the general public about the real life impact of HZ and PHN and their often severe, debilitating consequences and the potential benefits from vaccination.